2020
DOI: 10.1073/pnas.1922366117
|View full text |Cite
|
Sign up to set email alerts
|

Human TRIM5α senses and restricts LINE-1 elements

Abstract: Mobile genetic elements have significantly shaped our genomic landscape. LINE-1 retroelements are the only autonomously active elements left in the human genome. Since new insertions can have detrimental consequences, cells need to efficiently control LINE-1 retrotransposition. Here, we demonstrate that the intrinsic immune factor TRIM5α senses and restricts LINE-1 retroelements. Previously, rhesus TRIM5α has been shown to efficiently block HIV-1 replication, while human TRIM5α was found to be less act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(52 citation statements)
references
References 58 publications
2
48
0
Order By: Relevance
“…These recent studies further underline the capacity of huTRIM5α to potentially restrict HIV-1 in other relevant human target cells such as DCs, CD4 + T cells, and macrophages. Thus, efficient huTRIM5α restriction likely depends on TRIM5α subcellular localization (e.g., nucleus versus cytosol) within specific cell or tissue types, but also on the ability to induce autophagy- and immunoproteasome-facilitated degradation pathways, the presence of additional cellular factors that facilitate the action of huTRIM5α (e.g., Langerin), and the absence or inhibition of cellular factors that block huTRIM5α recognition of the viral capsid (e.g., CypA) [ 62 , 64 , 65 , 186 ].…”
Section: Hiv-1 Escapes Hutrim5α-mediated Restriction In Submucosalmentioning
confidence: 99%
See 2 more Smart Citations
“…These recent studies further underline the capacity of huTRIM5α to potentially restrict HIV-1 in other relevant human target cells such as DCs, CD4 + T cells, and macrophages. Thus, efficient huTRIM5α restriction likely depends on TRIM5α subcellular localization (e.g., nucleus versus cytosol) within specific cell or tissue types, but also on the ability to induce autophagy- and immunoproteasome-facilitated degradation pathways, the presence of additional cellular factors that facilitate the action of huTRIM5α (e.g., Langerin), and the absence or inhibition of cellular factors that block huTRIM5α recognition of the viral capsid (e.g., CypA) [ 62 , 64 , 65 , 186 ].…”
Section: Hiv-1 Escapes Hutrim5α-mediated Restriction In Submucosalmentioning
confidence: 99%
“…In addition to huTRIM5α sensing of exogenous retroviruses such as HIV-1, recent data suggest that the hypothesis that TRIM5α evolution was driven by retroelements, or endogenous retroviruses, is well-founded [ 186 , 198 , 199 ]. Notably, huTRIM5α was shown to both sense and restrict LINE-1 transposable elements, the only known autonomously active transposable element in humans, in HEK 293T cells [ 186 ]. Functional SPRY and B-box domains were essential for huTRIM5α-mediated inhibition of LINE-1 replication and insertion into the host genome.…”
Section: Trim5 As An Innate Immune Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we identified a novel retroelement-specific trigger of innate immune signaling. Our study demonstrated that the intrinsic restriction factor human tripartite motif-containing 5α (TRIM5α) senses and inhibits LINE-1 retrotransposition [ 109 ]. Previously, TRIM5 proteins have been shown to restrict exogenous retroviruses in a species-specific manner (reviewed in [ 110 ]).…”
Section: Immunogenic Patterns In Line-1mentioning
confidence: 99%
“…The signaling events activate the transcription factors AP-1 and NF-κB, leading to the downregulation of LINE-1 promoter activity, most likely indirectly by activating additional inhibitory factors. Together, we identified LINE-1 as target of TRIM5α, which restricts and senses LINE-1 RNPs in the cytoplasm, leading to inactivation of its promotor via a negative feedback loop, thereby protecting the genome from excess LINE-1 activity [ 109 ].…”
Section: Immunogenic Patterns In Line-1mentioning
confidence: 99%